HIV-Associated Hodgkin's Lymphoma: Prognosis and Therapy in the Era of cART - Caron A. Jacobson; Jeremy S. Abramson (Advances in Hematology)
Patients with human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) are at increased risk for developing Hodgkin's lymphoma (HL), a risk that has not decreased despite the success of combination antiretroviral therapy (cART) in the modern era. HIV-associated HL (HIV-HL) differs from HL in non-HIV-infected patients in that it is nearly always associated with Epstein-Barr virus (EBV) and more often presents with high-risk features of advanced disease, systemic “B” symptoms, and extranodal involvement. Before the introduction of cART, patients with HIV-HL had lower response rates and worse outcomes than non-HIV-infected HL patients treated with conventional chemotherapy. The introduction of cART, however, has allowed for the delivery of full-dose and dose-intensive chemotherapy regimens with improved outcomes that approach those seen in non-HIV infected patients. Despite these significant advances, HIV-HL patients remain at increased risk for treatment-related toxicities and drug-drug interactions which require careful attention and supportive care to insure the safe administration of therapy. This paper will address the modern diagnosis, risk stratification, and therapy of HIV-associated HL.